Determination of Trifluoperazine Hydrochloride in Pure form and Dosage form via Reaction with Sulphanilic Acid Diazonium Salt - Sahar Rihan Fadhel (Journal of Global Pharma Technology, 2019)
A simple and sensitive spectrophotometric method for determination trace amount of Trifluoperazine Hydrochloride in tablet pharmaceutical preparations were described. The method was based on the coupling reaction of drug with (0.25 mole.L-1) diazonium salt prepared from reaction of sulphanilic acid with (12.07 mole.l-1) hydrochloric acid at (0-5Cº) present sodium nitrite in basic medium of sodium hydroxide (0.1 mole.l-1) to produce orange color azo dye compound can be absorbed at 500nm, the optimum reaction conditions and other analytical parameters were evaluated. The high accurate and precise results obtained with RSD%, Recovery%, ere% and D.L were 0.8142, 100.019, 0.0574, and1.1205 µg.ml-1 respectively, the linearity of rang (5.0-140 µg.ml-1). The proposed methods were successfully applied to the determination of Trifluoperazine Hydrochloride in tablet pharmaceuticals without any effect of interference of chemical materials in tablet formulation.Keywords: Trifluoperazine Hydrochloride, sulphanilic acid, spectrophotometry, azo dye coupling.